지능형 UAV를 위한 임무 패키지 관리 및 실시간 상황 모니터링 통합개발환경 설계 및 구현 - 조연제; Yeon-je Cho; 전상우; Sang-woo Jeon; 신주철; Ju-chul Shin; 김경태; Gyeong-tae Kim; 김성우; Seong-woo Kim (한국항행학회논문지, 2025)
최근 UAV (unmanned aerial vehicle)는 빠른 속도로 성장해왔고, 재난 대응, 환경 모니터링뿐만 아니라 군사용으로도 널리 사용하기에 이르렀다. UAV 는 전장에서는 필수불가결한 존재라고 평가받았고, 이에 대해 지능형 UAV에 대한 연구가 더욱 활발해졌다. 지능형 UAV의 운용에 있어서 임무 패키지 생성, 검증, 배포가 중요한 요소이고, 이 일련의 과정의 안정적인 개발이 필요하다. 본 논문에서는 지능형 UAV의 자율 임무 수행을 지원하기 위해 AMAD (autonomous mission agents for drones) 아키텍처 기반의 통합개발환경(IDE; integrated development environment )을 제안한다. 제안된 IDE는 고수준 상황추론 규칙 및 작업 계획을 개발하며 임무 패키지 생성, 검증, 배포를 간소화한다. Recently, unmanned aerial vehicles have experienced rapid growth and are now widely used not only for disaster response and environmental monitoring but also for military applications. unmanned aerial vehicles (UAVs) are now regarded as indispensable assets on the battlefield, leading to increased research interest in intelligent UAVs. In operating intelligent UAVs, the generation, verification, and deployment of mission packages are critical components, and a stable development process for these tasks is essential. This paper proposes an integrated development environment (IDE) based on the autonomous mission agents for drones architecture to support autonomous mission execution of intelligent UAVs. The proposed IDE facilitates the development of high-level situation reasoning rules and task plans, and simplifies the process of generating, verifying, and deploying mission packages.